Responsiveness of local government officials: insights and lessons from participatory planning and budgeting. Issue 2 (2nd April 2020) - Panday, Pranab Kumar; Chowdhury, Shuvra
Abstract : Ensuring effective service delivery to the citizens has become a common agenda for all the governments of the welfare states. Keeping this importance in mind, the government of Bangladesh enacted the Local Government ( Union Parishad ) act, 2009 (hereinafter the UP act, 2009) for ensuring people's access to its local level planning and budgeting process. In this connection, the UP functionaries are responsible to perform double roles: ensuring the participation of people in the participatory planning and budgeting process, and providing services as per their demands. This paper is based on data collected from the UP functionaries of a total of six UPs. A questionnaire was developed having nine statements relating to the roles of the UP functionaries about UP planning and budgeting process. Using factor analysis, this study shows that three important capacities of the UP functionaries, including the capacity to inform citizens, compliance responsibilities and organising and networking among actors, made planning and budgeting processes workable at the local level. It was also revealed that along with legal enforcement; monitoring of the processes by the government and donor's officials and personal quality of the UP functionaries had made them responsiveness to their duties.